Erythema nodosum induced by kerion celsi of the scalp in a child: a case report and mini‐review of literature. Issue 3 (4th November 2012) - Castriota, Marina; Ricci, Francesco; Paradisi, Andrea; Fossati, Barbara; De Simone, Clara; Capizzi, Rodolfo; Guerriero, Cristina
Summary A 9‐year‐old girl, presented with a 4‐week history of an inflammatory suppurative plaque, 8 cm in diameter, localised in the occipital area of the scalp. Mycological direct examination showed ectoendothrix invasion of the hair and Trichophyton mentagrophytes was isolated. Oral therapy with griseofulvin 25 mg kg−1 day−1 was prescribed, but after 2 weeks of treatment appeared multiple erythematous subcutaneous nodules localised in the legs. Erythema nodosum (EN) was confirmed by histological examination of a nodule and then we combined therapy with 1 mg Kg−1 day−1 of prednisone. At the remission of the panniculitis, which occurred in about 10 days, the steroid therapy was suspended, while the orally administered griseofulvin continued for 6 weeks until full recovery. EN is the most frequent clinical form of acute nodular panniculitis and it is considered an epiphenomenon relative to various infectious and non‐infectious stimuli. The association of EN with dermatophytosis of the scalp is infrequent, with only 15 cases reported in the Literature.